Tradisi Pendidikan Keislaman di Pesantren Sunan Drajat Lamongan - Ulum, Miftachul; Mun'im, Abdul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This study aims to describe the educational tradition carried out at the Sunan Drajat Lamongan Islamic Boarding School. This qualitative research method was carried out by conducting a direct survey and exploring the documentation used in educational activities at the Sunan Drajat Lamongan Islamic Boarding School. The results of the study stated that academic and non-academic activities that have been scheduled are daily, weekly, monthly and annually at the Sunan Drajat Islamic Boarding School as a form of Islamic education tradition at the Sunan Drajat Lamongan Islamic Boarding School. These traditional activities can foster a sense of social sensitivity, spirituality and exemplary spirit in forming students who have good morals.